Pelatihan Pembuatan Singsaras (Singkong Disawut Menjadi Beras) untuk Mewujudkan Ketahanan Pangan di Desa Mojokrapak Tembelang Jombang - Waslah Waslah; Kurota Ayuna Pinda Rosuli; Rahmad Kurniawan; Riky Tedy Jamrud (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2021)
The implementation of the Singsaras product manufacturing training program in order to realize food security in Mojokrapak village was carried out at the Mojokrapak village hall, Tembelang Jombang, based on a survey, namely due to uneven economic conditions, there are still many community potentials that cannot be explored. The aims are : Increasing members of Family Welfare Development, empowering Family Welfare Development to achieve mutual prosperity and increasing the utilization of agricultural products in Mojokrapak Tembelang village, Jombang. The methods used are socialization, training and mentoring. The result of this activity is that this singsaras product can be a solution to realize food security and shared welfare in the village of Mojokrapak Tembelang, Jombang, East Java